Evaluation of the World Bank Group's Investment Climate Programs : Focus on Impact and Sustainability - Economisti Associati (World Bank, Washington, DC, 2015)
This impact evaluation reviews the investment climate (IC) reform programs implemented by the World Bank Group (WBG) in Burkina Faso, Liberia, Rwanda, Sierra Leone, and South Sudan. It follows a study carried out in 2011 across the same countries. The purpose of the evaluation is to update, expand, and deepen the initial analysis within the framework of the earlier study, in order to gain a better understanding of the impact and sustainability of the IC reform activities implemented by the WBG. The evaluation covers a total of 25 IC-related projects implemented by the WBG in the five countries since the mid-2000s. The evaluation consists of three main elements, namely: a review of the outcomes achieved by the IC programs; an analysis of how IC reforms translate into impacts that is into tangible benefits for private firms and for the economy as a whole; and an assessment of the sustainability of IC reforms. The result is a significant improvement in the overall quality of the business environment in the five countries. This report is structured as follows: section one gives introduction. Section two provides an overview of the context in which the WBG programs were implemented, with a short presentation of the salient features of the five countries; section three briefly reviews the activities undertaken by each WBG program; section four analyzes the outcomes of the IC reform programs, with a review of the reforms supported, of the influence of these reforms on the business environment, and of the private sectors perceptions of IC reforms; section five reviews in detail the impact of IC reform programs, providing estimates of both direct impacts (cost savings) and indirect impacts (changes in enterprise formation and formalization, investment, and employment); section six analyzes the sustainability of IC reforms, with respect to both current and prospective sustainability and with an analysis of the main factors influencing sustainability; and finally, section seven summarizes the key findings of the evaluation.